SEASONAL CHANGE OF THE ATMOSPHERIC HEAT BUDGET OVER THE SOUTHERN OCEAN FROM ECMWF AND ERBE DATA IN 1988 - オカダ, イタル; ヤマノウチ, タカシ; OKADA, Itaru; YAMANOUCHI, Takashi (National Institute of Polar Research, 1995)
P(論文) Seasonal change of the atmospheric heat energy budget in the Antarctic sea ice area in 60°S-70°S latitudinal belt in 1988 is obtained from ERBE radiation data and ECMWF global atmospheric data. Seasonal change of the net radiation at the top of the atmosphere, temporal change rate of static energy, convergences of meridional heat energy transport, and the surface heat energy flux are analyzed. To obtain atmospheric heat transport, two methods of correction are adopted. Net radiation at the top of the atmosphere heats the atmosphere in December and January, and cools it in the rest of the year with a negative maximum of -170W/m^2. The temporal change rate of static energy is positive in the former half of the year and negative in the latter half. Its amplitude is much less than those of other components. Convergences of meridional heat energy transport are uncertain about the yearly averaged level, but their seasonal cycle has two maxima (minima) in April and August (May and October) in which the circumpolar trough is located in higher (lower) latitude and is deeper (shallower) with lag of ±1 month. The surface heat energy flux which was obtained as a residual of other terms is maximum in May and minimum in December or January with amplitude of about 200-230W/m^2. It takes positive values, at least, during 8 months of the year from March to October. The surface heat flux decreases 33-68W/m^2 from May to July, by which time solar incidence is near zero. Change of cloud amount only cannot explain this reduction. Meanwhile, sea ice concentration increases from 33% to 60%. This increase of sea ice appears to affect to the change of the surface heat flux. In this area, there are few observational data that can be directly compared with the present result. However, by combining observational data and assumptions for radiation term and surface condition, our estimation for the surface heat flux is within the scattering of the observations in autumn. departmental bulletin paper